Pengaruh Penerapan Pendekatan Realistik Bidang Studi Matematika Terhadap Hasil Belajar Siswa Kelas IV Di SDN Birowo 02 Kabupaten Blitar - Fitri ayu andraini; Miftahul Muin (Kilau Publishing, 2023)
The reality in the field shows that fourth grade elementary school students still do not know the concepts and operations of fractions correctly. This can be because the mathematics learning process and methods used by teachers are not suitable for students' needs. As a result, students' ability to absorb material is not optimal and the results of student learning there was a decline. The aim of this research is to determine the effect of the Realistic approach on student learning outcomes in Class IV mathematics at SDN Birowo 02 Blitar Regency. This type of research is classroom action research using two cycles. Data collection uses observation, documentation and test techniques. Data analysis used qualitative data analysis techniques. The results of this research resulted in an increase in student learning outcomes through improving the learning process starting from Cycle I and Cycle II, from an average score of 70 which increased to 98.